2022
DOI: 10.1007/s13593-022-00764-w
|View full text |Cite
|
Sign up to set email alerts
|

Designing high-yielding wheat crops under late sowing: a case study in southern China

Abstract: Cropping of rice and wheat (Triticum aestivum L.) in rotation contiguously in the same field is a fundamental pillar of double-cropping systems in southern China. Yields of such cropping systems are increasingly challenged as climate change (CC) drives increases in autumnal rainfall, delaying rice harvesting and subsequent sowing of wheat. Here, our purpose was to identify prospective traits of wheat crops enabling adaptation to later sowing and successively truncated growing seasons caused by CC. To identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…We found that low Se concentration increased the SPAD value of sweet potato seedling leaves, consistent with this study, low Se concentration increased the chlorophyll content of lettuce ( Xue et al, 2001 ; Liu et al, 2022 ). Hawrylak-Nowak (2009) reported that the increase in chlorophyll content due to the effective scavenging of reactive oxygen species (ROS) caused by the addition of Se.…”
Section: Discussionsupporting
confidence: 91%
“…We found that low Se concentration increased the SPAD value of sweet potato seedling leaves, consistent with this study, low Se concentration increased the chlorophyll content of lettuce ( Xue et al, 2001 ; Liu et al, 2022 ). Hawrylak-Nowak (2009) reported that the increase in chlorophyll content due to the effective scavenging of reactive oxygen species (ROS) caused by the addition of Se.…”
Section: Discussionsupporting
confidence: 91%
“…First, while tiller number determines canopy densities during early development, not all tillers survive to maturation ( Davidson and Chevalier, 1990 ). The rate of the productive tiller development is regulated by manifold environmental factors, including soil temperature ( Thorne and Wood, 1987 ; Liu et al, 2022 ), soil water ( Tao et al, 2007 ), soil nutrient supply ( Longnecker et al, 1993 ; Scharf and Alley, 1993 ), and defoliation ( Harrison et al, 2012 ). For instance, Shang et al (2020) reported that adequate water supply at jointing stage can effectively reduce the tiller mortality and thus increase wheat yield.…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of GEI is helpful to evaluate genotype stability and adaptability across environments, recommend certain genotypes for specific growing environments, and assess the ability of test environments to discriminate the tested genotypes (Yan and Tinker, 2006;Dias et al, 2018). Several models of stability analysis are provided to elucidate the complex nature of GEI phenomena under stressed environments (Mafouasson et al, 2018;Liu et al, 2022) and to utilize the obtained information for varietal selection (Kang, 1998;Liu et al, 2020a). These models include joint regression analysis (Finlay and Wilkinson, 1963;Eberhart and Russell, 1966), the additive main effects and multiplicative interaction (AMMI) (Gauch, 1992), and the genotype main effects and genotype × environment interaction (GGE) biplot analysis (Yan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%